Fractionated stereotactic radiotherapy (FSRT) for optic glioma - Debus, Jürgen; Kocagöncü, K. Oktay; Höss, Angelika; Wenz, Frederik; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 1999)
Purpose: To determine efficacy and toxicity of fractionated stereotactic radiotherapy (FSRT) in patients with optic glioma. Methods and Materials: Ten patients suffering from optic glioma were treated by FSRT between December 1990 and December 1995 at the German Cancer Research Center (DKFZ) in Heidelberg. Eight patients were treated for progressive recurrent tumor following partial tumor resection and 2 patients were treated postoperatively. Dose distributions were calculated by a 3D treatment planning system (Voxelplan, Heidelberg). Patients were treated with a noninvasive repeatable stereotactic fixation system using a manually driven midsize multileaf collimator attached to a linear accelerator. We applied a median prescribed total dose to the isocenter of 52.4 Gy with a median daily fraction size of 1.8 Gy Results: All patients treated by definitive radiotherapy remained free from local tumor progression during the follow-up period (range 12-72 months) except the 1 patient treated for recurrence after previous radiotherapy. A complete remission was achieved in 3 patients with subsequent improvement of visual acuity. None of the patients with locally controlled tumor experienced any further impairment of vision. One patient developed new ACTH deficiency. No other clinically significant late effects attributable to radiotherapy were observed. Conclusion: FSRT permits treatment of optic glioma with excellent tumor control and without clinically relevant morbidity. Compared to conventional techniques there is the potential of sparing the pituitary gland in chiasmatic lesions.
Gesehen am 22.03.2022